INTEGRATING ETHNOFORESTRY AND REMOTE SENSING FOR A HOLISTIC ASSESSMENT OF FOREST HEALTH AND COMMUNITY WELL-BEING IN PAPUA - Soleman, Christian; Angrianto, Novaldi Laudi; Kesauliya, Olivia Marie Caesaria (Journal of Selvicoltura Asean, 2025)
Conventional remote sensing often fails to capture the full picture of forest health, ignoring the nuanced knowledge of indigenous communities intrinsically linked to the environment. This study's objective was to develop a holistic framework for assessing forest health by integrating indigenous Papuan ethnoforestry knowledge with advanced remote sensing techniques, and analyzing the link to community well-being. A mixed-methods approach was employed, combining participatory mapping and interviews (collecting local indicators) with time-series analysis of Landsat imagery (deriving biophysical metrics like NDVI). The findings showed a strong positive correlation between community perception and satellite indices. Crucially, the integrated approach revealed subtle degradation (e.g., loss of culturally significant species) undetectable by remote sensing alone. A direct link was established between this degradation and a decline in community well-being (e.g., access to traditional medicine). This integrated framework provides a more accurate and socially relevant assessment, enhancing monitoring, empowering local communities for co-management, and ensuring sustainable livelihoods.